- Pelatihan Kader Posyandu tentang Kebutuhan Gizi Bagi Ibu Hamil dan Balita di Kelurahan Tirta Siak Pekanbaru - Hutabarat, Sakti; Marpaung, Noveri Lysbetti; Ervianto, Edy; Nurhalim, Nurhalim; Amri, Rahyul (Journal of Community Engagement Research for Sustainability, 2022)
One healthy problem related to somebody’s physic that can not grow-up well is Stunting. Stunting is someone’s condition whereas less level of nutrient occurs in long time. Therefore, it causes nutrient problem cronically. Stunting be marked with growth of height of children which are not suitable with standar of their ages. One way to prevent stunting on toddler early is by increasing knowledge of a mother/pregnant-woman about nutrient, through nutrient education. Aim of this service is to educate craders of healthy facility, Posyandu, in Tirta Siak Village about nutrient requirement for pregnant-woman and Toddler to prevent stunting earlier in communities around Posyandu. Methodology of this service is performing training for Posyandu’s craders to give right understanding about standardization of nutrient need for pregnant-woman and toddler and to prevent stunting earlier, even since that baby in the womb. This training gets full support from PPKBD’s chairwoman, leader for all posyandus in Tirta Siak Village. Participants are enthusiastic to follow training. Hopefully, Posyandu’s craders can implement obtained knowledge about nutrient requirements for pregnant-woman and toddler to society.